2015
DOI: 10.1038/srep08803
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of PLA2R autoantibodies and glomerular staining for the differentiation of idiopathic and secondary membranous nephropathy: an updated meta-analysis

Abstract: The diagnostic performance of M-type phospholipase A2 receptor (PLA2R) autoantibodies and PLA2R glomerular staining in discriminating between idiopathic membranous nephropathy (iMN) and secondary membranous nephropathy (sMN) has not been fully evaluated. We conducted an updated meta-analysis to investigate the accuracy and clinical value of serological anti-PLA2R test and histological PLA2R staining for differentiation iMN from sMN. A total of 19 studies involving 1160 patients were included in this meta-analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 32 publications
3
69
1
2
Order By: Relevance
“…Circulating PLA2R antibodies seem to be specific for pMN [32-34]; however, they can also occur in secondary MN, especially the hepatitis B virus-related MN common in China [35]. The prevalence of positive antibodies varies between different diagnostic centers, from the highest prevalence of 82% [36] to the lower prevalences of 68% [37], 59% [38], and 69% [39], respectively, in China.…”
Section: The Autoimmune Disorders Of Pmnmentioning
confidence: 99%
“…Circulating PLA2R antibodies seem to be specific for pMN [32-34]; however, they can also occur in secondary MN, especially the hepatitis B virus-related MN common in China [35]. The prevalence of positive antibodies varies between different diagnostic centers, from the highest prevalence of 82% [36] to the lower prevalences of 68% [37], 59% [38], and 69% [39], respectively, in China.…”
Section: The Autoimmune Disorders Of Pmnmentioning
confidence: 99%
“…4 sMN could be induced by various conditions, such as malignancies (breast, ovarian, lung, and stomach cancers, and lymphoproliferative disorders), infections (human immunodeficiency virus, malaria, hepatitis B and C viruses), some systemic autoimmune diseases (rheumatoid arthritis and lupus), and the consumption of drugs and toxins. 5,6 MN is characterized by non-selective proteinuria, with the nephrotic range of more than 3.5 g/day.…”
Section: Introductionmentioning
confidence: 99%
“…This study found an overall sensitivity, specificity, diagnostic odds ratio and ROC-AUC of serum anti-PLA2R to be 0.68 (95% CI, 0.61-074), 0.97 (95% CI, 0.85-1.00), 73.75 (95% CI, 12.56-432.96) and 0.82 (95% CI, 0.78-0.85), respectively, with substantial heterogeneity (I 2 = 86.42%) between the studies . [20] Another similar study for PLA2R displayed 99% specificity and 78% sensitivity for the diagnosis of primary MN with tissue staining and serology distinguishing most cases of primary MN from secondary . [21] Larsen et al in his series of 85 primary MN and 80 secondary MN found sensitivity of 75% (95% CI: 65−84%) and specificity of 83% (95% CI: 72−90%).…”
Section: Performance Of Pla2r As Diagnostic Toolmentioning
confidence: 99%
“…Subgroup analysis by Huanzi Dai et al showed significant discrepancy between different forms of secondary MN with highest diagnostic accuracy when secondary MN was lupus MN. 20 We did not carry out subgroup analysis but all our cases of Lupus Nephritis Class V were negative for PLA2R.It suffices to say that clinical significance of anti-PLA2R1 antibodies in secondary MN with positive PLA2R staining requires wider sampling and screening is necessary for specific subgroups especially in older patients even if serological anti-PLA2R and/or histological PLA2R antigen is positive.…”
Section: Anti-pla2r Antibody In Primary Vs Secondary Mn Vs Control Grmentioning
confidence: 99%